If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + -88 = 4(-2x + -7) Reorder the terms: -88 + 12x = 4(-2x + -7) Reorder the terms: -88 + 12x = 4(-7 + -2x) -88 + 12x = (-7 * 4 + -2x * 4) -88 + 12x = (-28 + -8x) Solving -88 + 12x = -28 + -8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8x' to each side of the equation. -88 + 12x + 8x = -28 + -8x + 8x Combine like terms: 12x + 8x = 20x -88 + 20x = -28 + -8x + 8x Combine like terms: -8x + 8x = 0 -88 + 20x = -28 + 0 -88 + 20x = -28 Add '88' to each side of the equation. -88 + 88 + 20x = -28 + 88 Combine like terms: -88 + 88 = 0 0 + 20x = -28 + 88 20x = -28 + 88 Combine like terms: -28 + 88 = 60 20x = 60 Divide each side by '20'. x = 3 Simplifying x = 3
| 4x+21=29 | | 3s/5=21 | | 3(25x+80)=-2(15x-15) | | 2(x+10)=2x+10 | | 2[1.65]+13.86+6.93=12.54 | | 4x-4=-4(-x+1) | | (1.3g+3)(4g+5)= | | -5+14x=7(2x)-5 | | (3n+5)(4n+5)= | | -6x+1=-3(2x+1)+x | | 6y+11=43 | | X^2-15x+12=-6+4 | | 5x-3(x-1)-39= | | (2+3c)(4+6c+9c)= | | (2a-1)(a+3a+5)= | | 435*13= | | X+3=-3-5 | | 46.1*46.1=18.5*18.5+2(11.17)x | | 2(3x-5)=-(x-11) | | 2s-2=2 | | (a+2a-9)(a+3)= | | -15.00+2.00w=5 | | 12+7y-2=52 | | (y+3y-6)(2y+3)= | | 0=2x^2+6kx+8 | | 7r^2-14r-7=0 | | A=5W+10Z | | 2.00r-15.00=9 | | 12x-8=16x+4 | | 4x^2-3=x^2-11x | | (3x+2y)(2y+3x)= | | -4g+6=14 |